2022
DOI: 10.3390/ijms23063005
|View full text |Cite
|
Sign up to set email alerts
|

The miRNA-21-5p Payload in Exosomes from M2 Macrophages Drives Tumor Cell Aggression via PTEN/Akt Signaling in Renal Cell Carcinoma

Abstract: M2 macrophages in the tumor microenvironment are important drivers of cancer metastasis. Exosomes play a critical role in the crosstalk between different cells by delivering microRNAs or other cargos. Whether exosomes derived from pro-tumorigenic M2 macrophages (M2-Exos) could modulate the metastatic behavior of renal cell carcinoma (RCC) is unclear. This study found that M2-Exos promotes migration and invasion in RCC cells. Inhibiting miR-21-5p in M2-Exos significantly reversed their pro-metastatic effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…M2-Exos-miR-21-5p promoted tumor metastasis in RCC. 35 In the avian embryo chorioallantoic membrane in vivo tumor model as well as in vitro , tumor metastasis was prevented by miR-21-5p knockdown in M2-TMAs-Exos. 35 Furthermore, M2-Exos-miR-487a significantly promoted tumor proliferation and progression in vitro and in vivo in GC.…”
Section: Interaction Between Gic and M2-tams-exos-ncrnas In The Tmementioning
confidence: 95%
See 2 more Smart Citations
“…M2-Exos-miR-21-5p promoted tumor metastasis in RCC. 35 In the avian embryo chorioallantoic membrane in vivo tumor model as well as in vitro , tumor metastasis was prevented by miR-21-5p knockdown in M2-TMAs-Exos. 35 Furthermore, M2-Exos-miR-487a significantly promoted tumor proliferation and progression in vitro and in vivo in GC.…”
Section: Interaction Between Gic and M2-tams-exos-ncrnas In The Tmementioning
confidence: 95%
“… 35 In the avian embryo chorioallantoic membrane in vivo tumor model as well as in vitro , tumor metastasis was prevented by miR-21-5p knockdown in M2-TMAs-Exos. 35 Furthermore, M2-Exos-miR-487a significantly promoted tumor proliferation and progression in vitro and in vivo in GC. 51 Adding to that, Exos-miR-365 secreted by M2-TMAs was reported as a significant promoter of PDAC progression by downregulating the expression of BTG2, leading to the promotion of FAK/AKT signaling.…”
Section: Interaction Between Gic and M2-tams-exos-ncrnas In The Tmementioning
confidence: 95%
See 1 more Smart Citation
“…A similar protocol was presented by He et al in a study investigating the role of exosomal miR-31-5p in the induction of resistance to sorafenib [12]. Assessment of the exosomal miRNA of the RCC microenvironment was recently shown to be relevant, as pro-tumorigenic miRNAs were found in exosomes related to the cross-talk between cancer cells and polarized M2 macrophages [13][14][15]. miRNAs directly secreted into the plasma by RCC tumor or stromal cells have also been proven to be stable in humans and were reliably isolated via RT-qPCR of a centrifuged miRNA phase [16][17][18].…”
Section: Mirna Isolationmentioning
confidence: 96%
“…Yang et al reported ( 20 ) that exosomal miR-487a derived from M2 macrophages promotes gastric cancer progression by regulating T-cell intracellular antigen 1 (TIA1). Zhang et al found ( 21 ) that exosomes derived from M2 macrophages carrying miR-21-5p promote renal cell carcinoma (RCC) cell invasion by the activation of the Phosphatase and TENsin homolog (PTEN)/protein kinase B (Akt) RCC cell signaling pathway. Long et al suggested ( 22 ) that M2 exosomes carrying miR-1271-5p attenuate apoptosis in cardiomyocytes and promote cardiac repair by downregulating SRY-box containing gene 6 (SOX6) expression.…”
Section: Introductionmentioning
confidence: 99%